TERMS DICTIONARY COMPUTER APPLICATIONS USING VISUAL BASIC 6.0 SOFTWARE - Diana Desy (JAKSTIK Journal, 2005)
Every field of science have their own terms in the fields of science, as well as a lot ofcomputer science that there are terms in it, generally only those who learn the computer onlyunderstands these terms. To help find out the computer terms, the writer tries to make theApplication Dictionary of Computer Terms with Visual Basic 6.0. Discussion